2023
DOI: 10.1002/cpp.2834
|View full text |Cite
|
Sign up to set email alerts
|

The lived experience of adolescent depression: A systematic review and meta‐aggregation

Abstract: Background The under‐detection of depression in adolescents suggests that a better understanding of its presentation may be needed. Conceptualizations of adolescent depression are largely the same as adult depression, with minimal consideration of developmental stage. Exploration of first‐hand accounts could help to identify any unique features of adolescent depression. Therefore, this systematic review aimed to understand the lived experience of adolescents with depression to inform clinical practice. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 84 publications
0
8
0
Order By: Relevance
“…In addition, one of the study's key findings was that the younger the age the more extreme the scale of depression. Age-related variations in symptom frequency of depression have been found (Twivy, Kirkham & Cooper, 2023). Table 2 below showed the profile of the respondents in accordance with their choice of gender.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, one of the study's key findings was that the younger the age the more extreme the scale of depression. Age-related variations in symptom frequency of depression have been found (Twivy, Kirkham & Cooper, 2023). Table 2 below showed the profile of the respondents in accordance with their choice of gender.…”
Section: Resultsmentioning
confidence: 99%
“…Two prior studies have reported comparable results regarding the utilization of social media in non-pandemic periods and gaming during the COVID pandemic as coping mechanisms among depressed adolescents. [ 5 , 30 ] In addition, previous quantitative research has shown a correlation between depression in adolescents and extended gaming time during the COVID pandemic. [ 31 ] Furthermore, depression has been found to influence the impact of family conflicts on problematic internet use.…”
Section: Discussionmentioning
confidence: 99%
“…Similar descriptions of ruminations, [ 34 ] fatigue, [ 27 ] and lack of motivation have been reported in other studies involving depressed adolescents. A recent review reported three subthemes in adolescents’ attributions to causes of depression: “environmental influences,” “internal causes,” and “difficulty understanding.” [ 5 ] Similar to the third subtheme, the study participants were uncertain about the cause but identified stress as a possible cause. All participants perceived the worsening and prolongation of depression during the pandemic and this study is the first to report this subjective finding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of mental health management in reducing depressive symptoms in young adults has been highlighted [11,23], yet, as noted, managing depression can have several unintended consequences for both teenagers and their parents, such as powerlessness and trauma [24]. According to a different study, adolescents with depression constantly worry about relapsing despite ongoing treatment [25]. These incidents, however, go against how youth receiving depression treatment should perceive themselves, challenging their sense of self [26].…”
Section: Introductionmentioning
confidence: 99%